25.5k views
3 votes
Write the expression as a as a single logarithm 5log2+log3=

User Anass
by
5.6k points

1 Answer

4 votes

Solution:

Given the expression;


5\log_(2+\log_(3

Following addition and power property of logarithm;


\begin{gathered} a\log_b=\log_b^a \\ \\ \log_a+\log_b=\log_ab \end{gathered}

Thus;


\begin{gathered} 5\log_(10)2+\log_(10)3=\log_(10)2^5+\log_(10)3 \\ \\ 5\log_(10)2+\log_(10)3=\log_(10)32+\log_(10)3 \\ \\ 5\log_(10)2+\log_(10)3=\log_(10)(32*3) \\ \\ 5\log_(10)2+\log_(10)3=\log_(10)96 \end{gathered}

ANSWER:


\log_(10)96

User Kirtiman Sinha
by
6.6k points